2017
DOI: 10.1021/acs.inorgchem.7b02264
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Luminescent Metal-Organic Frameworks: Structural Diversification, Photophysical Properties, and Sensing Applications

Abstract: Utilizing flexible bis(tridentate)polypyridyl ligands, the two new luminescent 2D metal organic frameworks {Zn(tpbn)(2,6-NDC)} (1) and {[Zn(tphn)(2,6-NDC)]·4HO} (2), where tpbn = N,N',N″,N‴-tetrakis(2-pyridylmethyl)-1,4-diaminobutane, tphn = N,N',N″,N‴-tetrakis(2-pyridylmethyl)-1,6-diaminohexane, and 2,6-HNDC = 2,6-naphthalenedicarboxylic acid, have been isolated in good yields under solvothermal conditions. Their solid-state molecular structures have been determined by single-crystal X-ray diffractometry. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 58 publications
5
52
0
Order By: Relevance
“…Since both the values are close to 0, it confirms that both have more towards square pyramidal geometry . It is noteworthy to observe that 1 is dinuclear compound instead of a polymeric framework as obtained in case of {Zn 2 (tpbn)(2,6‐ndc) 2 } n (where, 2,6‐ndc=2,6‐naphthalene dicarboxylate, a linear linker), a dinuclear complex is obtained which is due to the presence of a free carboxylate obstructing the growth of the polymer. However, very strong inter‐ and intramolecular H‐bonding interactions are present that leads to the formation of a 1D supramolecular assembly as shown in Figures b,c.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Since both the values are close to 0, it confirms that both have more towards square pyramidal geometry . It is noteworthy to observe that 1 is dinuclear compound instead of a polymeric framework as obtained in case of {Zn 2 (tpbn)(2,6‐ndc) 2 } n (where, 2,6‐ndc=2,6‐naphthalene dicarboxylate, a linear linker), a dinuclear complex is obtained which is due to the presence of a free carboxylate obstructing the growth of the polymer. However, very strong inter‐ and intramolecular H‐bonding interactions are present that leads to the formation of a 1D supramolecular assembly as shown in Figures b,c.…”
Section: Resultssupporting
confidence: 53%
“…On the basis of systematic studies, we have recently demonstrated the role of the flexible chain length in the bis(tridentate)polypyridyl capping ligands that connect the two metal ions in the formation of diverse MOFs . Using d 10 metal ions (Zn 2+ and Cd 2+ ) as well as fluorescent linkers containing π‐conjugated moieties (naphthalene and anthracene groups), we continue to develop LMOF sensors for the detection of NACs . In these three‐component systems, we explore our efforts to showcase the effect of shape (linear vs. bent) and an increase in the number of π‐conjugated moieties in the dicarboxylate linkers on their sensing abilities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Zn-N bond lengths are slightly longer than the Zn-O bonds, with values of 2.054(4) and 2.072(4) Å. These values are similar to other Zn(II) compounds with Zn-O coordination through carbonyl groups [54][55][56] or carboxylate ligands which display monodentate coordination modes in combination with pyridine derivative ligands [57,58].…”
Section: (1) Intermolecular Interactions (å) D-h•••a D-h (å) H•••a (åsupporting
confidence: 57%
“…CPs based on 3-Hcptpy should have electron-rich architectures and usually exhibit strong luminescence peoperties, and can thus be developed as sensors for the detection of electron-deficient analytes, such as heavy-metal cations, nitro aromatic compounds (NACs) etc. (Chakraborty & Mandal, 2017). NACs, such as 2,4,6-trinitrophenol (TNP), 2,4-dinitrophenol (2,4-DNP), dinitrotoluene (DNT), 1,3-dinitrobenzene (1,3-DNB) and nitrobenzene (NB), have been widely used in ISSN 2053ISSN -2296 # 2019 International Union of Crystallography the military, dye, agriculture and pharmaceutical industries (Chaudhari et al, 2013;Sathish et al, 2017).…”
Section: Introductionmentioning
confidence: 99%